Diversifikasi Produk Stik Substitusi Kunir Putih di Karang Taruna Yodha Desa Argomulyo - Bayu Kanetro; Dwiyati Pujimulyani; Umul Aiman (Universitas Prof. Dr. Hazairin, SH, 2021)
Product Diversification of White Saffron Substitute Stick in Karang Taruna Yodha, Argomulyo Village Jogja Youth Farming (JYF) is an agro-tourism development carried out by Yodha youth organizations in Argomulyo Village, Sedayu, Bantul Regency, Special Region of Yogyakarta. Efforts are being made to develop JYF Agrotourism through downstream research. The survey results of the service team found that the Yodha youth organization had a potential to develop functional food entrepreneurs based on local rhizome plants (called as empon-empon) from the Argomulyo village area. In addition, around Agrotourism there are still many vacant fertile lands (idle land) that have not been used intensively. The purpose of this community service activity was to develop the entrepreneurial potential of the Yodha youth organization in Argomulyo Village. Development of potential by preparing the basic ingredients of empon-empon through good cultivation and processing of sticks, which are superior (have antioxidant activity) and are favored by consumers. The solution offered was to conduct training and practice on empon-empon cultivation and how to process it into functional food, sticks product. The JYF youth organization has produced sticks with the addition of empon-empon and sticks that consumers like with the addition of 10% white saffron.